Trauma, poisoning and envenomation caused by fish in Brazil: a review - Matheus M Novelli (Asociación Colombiana de Infectología, 2022)
Injuries caused by traumatic, poisonous and venomous animal are relatively common in the medical practice of many regions, especially in tropical countries, such as Brazil. These include morbid events caused by a wide variety of fish. Although they are generally of low severity, restricted to local manifestations of the place where the venom/poison comes into contact with the skin or mucosa, these illnesses can evolve to more severe conditions which, in rarer cases, can lead to death. The potential severity in some cases, along with the recent increase in the number of notifications, in different areas of the country, demonstrate the need for a better understanding of these events. Based on these considerations, the present article aims to review the literature on the main characteristics of trauma, poisoning and envenomation by fish in Brazil, with emphasis on the causative animals and on the pathophysiological, clinical and therapeutic aspects of these morbid conditions.